Synergistic anticancer effects of ABT-199 and Vorinostat encapsulated in PLGA nanoparticles: Formulation, characterization, and antiproliferative effects against colorectal cancer cells - Dina Raed Abu Alsamen; Zainab Zaki Zakaraya; Anas Abed; Alhareth A. Alsa’d; Maysoon Raed Alnajdawi (PLoS ONE, 2025)
The combination of ABT-199, a BCL-2 inhibitor, and Vorinostat, a histone deacetylase inhibitor, holds great potential in colorectal cancer therapy due to their synergistic effects. However, their poor solubility and bioavailability present challenges for effective treatment. This study aimed to co-encapsulate these drugs in poly(lactic-co-glycolic acid) nanoparticles to enhance stability, control drug release, and preserve their synergistic anti-proliferative effects in colorectal cancer cells. This study initially focused on evaluating the anti-proliferative activity of free ABT-199 and Vorinostat in HT-29 and HCT116 colorectal cancer cells. The drugs demonstrated potent cytotoxic effects, with Vorinostat exhibiting IC50 values of 1.32 µM in HT-29 cells and 2.04 µM in HCT116 cells, while ABT-199 displayed IC50 values of 4.04 µM and 5.49 µM, respectively. To investigate the interaction between ABT-199 and Vorinostat, the combination index was calculated using the Chou-Talalay method. The analysis revealed strong synergism between the drugs in both cell lines, with CI values consistently below 1 across all tested molar ratios. The most pronounced synergy was observed at a 1:1 molar ratio, which exhibited the lowest CI values. Building on these results, ABT-199-loaded nanoparticles (ABT-NPs), Vorinostat-loaded nanoparticles (VOR-NPs), and dual-loaded nanoparticles (DLNPs) were formulated using the nanoprecipitation method. ABT-NPs and VOR-NPs had sizes of 210.6 ± 6.2 nm and 202.5 ± 5.6 nm, with encapsulation efficiencies of 73.2 ± 4.81% and 86.4 ± 5.5%, respectively. The DLNPs, which co-encapsulated both drugs at a 1:2 molar ratio, exhibited a size of 210 ± 7.3 nm and maintained good stability. Cytotoxicity studies revealed that both ABT-NPs and VOR-NPs retained comparable anti-proliferative effects to the free drugs, with IC50 values close to those of their unencapsulated counterparts. Furthermore, DLNPs enhanced the anti-proliferative effect, significantly increased the apoptotic cells as measured by flow cytometry which was coincided with an increasing caspase-3 activity in both HT-29 and HCT116 cells, indicating an enhanced apoptotic response.